'Movie-made generation': cinema-going and the novel in post-war Britain - McLaughlin, M (2014)
This thesis examines how the reading and writing of the post-war British novel is altered by the emergence of an 'everyday' cinema-going culture amongst young people in the 1920s, 30s and 40s. The thesis demonstrates how viewing and reading practices converge in the twentieth-century and how the resulting modification of the visual literacy of this new, 'movie-made' generation of 'cinesthetic' writers and readers refigures realism in this period. Such cinesthetic realism can be differentiated from the modernist mode of the 'camera-eye' by how it elicits interactive (and often sexist) affects and leads to techniques such as 'indexical characterisation' and a consideration of 'extratextual' narratives. Thus, the thesis argues for the post-war period as one of literary innovation as opposed to the regressive, anti-modern epoch it is still widely labelled. The work encompasses a broad range of novels and novelists: 'Invitations to a Candy-Floss World?' explains how John Braine's 'documentary' fiction engages with cinematic escapism, how Colin MacInnes incorporates cinema-going as an emblem of marginalisation, and how Alan Sillitoe positions cinema as a 'valid' literary influence; 'I Could Have Bitten Her' examines the influence of Philip Larkin's addiction to cinema in his debut novel, John Wain's investigation of the cinesthetic reification of the post-war novelist, and Kingsley Amis' extratextual and (surprisingly) feminist endeavours; 'Passionate Detachment' explores Muriel Spark's employment of cinema to represent a crisis in feminine ipseity, Lynne Reid Banks' use of 'sexist' cinema as a proto-feminist trope (in conjunction with an interview with Banks), and Iris Murdoch's relationship with cinema as 'Plato's Cave', which leads to refigurations of realism and feminist forms of escape. Ultimately, this thesis aims to foreground an underestimated aspect of the transition between the 'late modernist' and the 'contemporary' in British fiction.